Viruses and acute abdominal pain in childhood. Issue 10 (October 1979) - Pullan, C R; Halse, P C; Sims, D G; Alexander, F W; Gardner, P S; Codd, A A
Abstract : Children aged at least 4 years admitted to hospital with acute abdominal pain, excluding appendicitis, were investigated for the presence of viruses. Out of 181 children 29 were found with viruses of whom 18 had nonspecific abdominal pain. Eight others were found to have virus-like particles on electron microscopical examination of their faeces. Virus infections contribute to a small extent to nonspecific abdominal pain in childhood, but in many cases the cause remains unknown.